PENGARUH BEBAN KERJA DAN FAKTOR LINGKUNGAN FISIK TERHADAP TEKANAN DARAH DAN DENYUT NADI PEKERJA BAGIAN ARC FURNACE DAN ROLLING MILL PT INTI GENERAL YAJA STEEL SEMARANG - Ulfa Nurullita (Jurnal Kesehatan Masyarakat Indonesia, 2007)
Background: The optimal work efficiency can be achieved if there is a beneficial balance of workload, added workload causecl by work environment, and work capacity. One of the factors of added workload caused by work environment is physical factor, such as air temperature, lighting, dampness, air rapidity, noise, mechanical vibration, radiation and air pressure. Metal foundry industry is closely related to dominant physicalenvironment factor, such as heat pressure, noise, and lighting. Those factors affect on one's physical performance especially workers' blood pressure and pulse. Objective of this research is to analyze lhe effect ofworkload and physical environment factor on workers'blood pressure, pulse, as well as fatigue level in Arc Furnace ancl Rolling Mill department, PT Inti General Yaja Steel Semarang. Method used in this research is thequasi experiment with one group pre and post test design. Research samples are 47 people who are selected by inclusion criteria. Heat pressure and noise are measured in the middle of first ffice hours at l0 a.m. approximately, while blood pressure and pulse are measurecl before and after working in the first ffice hours or at break hours. Result of this research shows that blood pressure in average before working is(systole:119,7 mmHg, diastole:84 mmHg), higher than afterworking (systole:107,2 mmHg, diastole:78,9 mmHg). The average of pulse before working is (8 1,5 times/minute), lower than after working (87,5times/minute). It can be concluded that there is difference of blood pressure before working and after working (systole; p- Wilcoxon Sign Ranks = 0,001, tliatole; p- ll/ilcoxon Sign Ranl<s,:0,003). There is dffirence of pulse before working and after working (p-paired t test: 0,001). Workers' blood pressure is degrading, while their pulse is rising, this is due to the fact that workers have already dealt with workload, heat pressttre and noise in work environment.Keywords: blood pressure, pulse, physical environment